C(sp2)-C(sp2) Suzuki cross-coupling of arylammonium salts catalyzed by a stable Pd–NHC complex. (8th October 2021) - Tang, Huiling; Liu, Mengna; Zhu, Meiqi; Cui, Benqiang; Shi, Yanhui; Cao, Changsheng
Abstract: We have developed the Suzuki-Miyaura cross-coupling of aryl ammonium salts via C–N bond activation catalyzed by an easily prepared and bench-stable palladium-N-heterocyclic carbene complex. The reaction proceeded well under mild conditions with phenylboronic acid, pinacol ester or anhydride and provided yields of products up to 97% with good functional group compatibility. The direct arylation of arylamine can be performed by a two-step one-pot process and the protocol can be performed on the gram scale. Graphical abstract: Image 1